2020
DOI: 10.21203/rs.2.24486/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Yolk Sac tumor differentiation in urothelial carcinoma of the urinary bladder: A case report and differential diagnosis

Abstract: Background: Yolk sac tumor (YST) is a germ cell neoplasm that arises predominantly in the gonads, but can also derive from somatic neoplasms in extragonadal locations. These latter cases have been documented in several organs, although reports from the urinary tract are limited. To our knowledge, this is the first report of a bladder urothelial carcinoma with a predominant component of YST differentiation.Case presentation: We present a unique case of a 76-year-old man with a recurrent urinary bladder tumor, i… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…Because of the limited number of reported cases, there is no consensus on standard treatment. In the prior case reported by Espejo-Herrera and Condom-Mundó, 3 the patient presented with thoracic mass at presentation, after surgery received chemotherapy cycles with poor response, and developed pulmonary and brain metastasis 9 months following cystectomy. The patient died 11 months after diagnosis.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Because of the limited number of reported cases, there is no consensus on standard treatment. In the prior case reported by Espejo-Herrera and Condom-Mundó, 3 the patient presented with thoracic mass at presentation, after surgery received chemotherapy cycles with poor response, and developed pulmonary and brain metastasis 9 months following cystectomy. The patient died 11 months after diagnosis.…”
Section: Discussionmentioning
confidence: 94%
“…Germ cell differentiation has been described in association with somatic tumors arising from several different organ systems 1-4 ; it is well established that urothelial carcinoma may show divergent differentiation, and several variants have been recognized by the 2016 World Health Organization (WHO) classification of urothelial carcinomas. 5 These include but are not limited to squamous, glandular, trophoblastic, neuroendocrine, nested, micropapillary, plasmacytoid, and sarcomatoid variants of urothelial carcinoma.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further more, HGUC with solid and papillary arrangements had histological overlaps and might mimic HACD just like this case which was initially misdiagnosed in the rst resection. Primary urothelial carcinoma of bladder with hepatoid features or yolk sac tumor differentiation had also to be distinguished from HACD and a close pathologic sampling and examination was necessary [11].…”
Section: Case Presentationmentioning
confidence: 99%
“…Besides, no abnormality was found by systemic imaging examinations which indicated that this patient should suffer a primary bladder cancer instead of secondary or metastatic HAC. Yamada [4] reported a HACD with urothelial carcinoma in situ in the mucosa proximal to the main tumor and more and more urothelial carcinoma with hepatoid features were reported [11,18,19]. Vail [20] reported that 72% of urothelial carcinoma with glandular differentiation had TERT promoter mutations, while primary adenocarcinoma of bladder had no TERT promoter mutations.…”
Section: Case Presentationmentioning
confidence: 99%